The Effectiveness of Guided Inquiry with Scaffolding Techniques in Enhancing Primary Students' Self-Efficacy in Mathematics - Vonitasari, Adinda Rheyna; Amir, Mohammad Faizal (FKIP Universitas Lampung, 2025)
Students' self-efficacy towards mathematics is still low. High self-efficacy is an essential factor in supporting learning success. Guided inquiry elaborated with scaffolding techniques is thought to affect students' self-efficacy. Therefore, this study aims to identify the effect of guided inquiry with scaffolding techniques on students' self-efficacy. The study design used was the posttest-only control group. In this study, data collection techniques were used using a questionnaire containing 20 questions to measure students' self-efficacy (magnitude, generality, and strength) in facing and completing mathematics tasks. Study participants included fourth-grade students' who were drawn through purposive sampling. ANOVA test and post hoc analysis were used for data analysis. The data analysis showed differences in students' self-efficacy between the implementations of guided inquiry with scaffolding techniques, guided inquiry without scaffolding techniques, and conventional learning. It was concluded that guided inquiry implemented with scaffolding techniques significantly enhanced students' mathematics self-efficacy. The most affected dimensions of self-efficacy from high to low are strength, magnitude, and generality. This shows sufficient scaffolding during the implementation of guided inquiry. In addition, students received sufficient scaffolding in the exploration process, which resulted in students being more confident in understanding the material and completing tasks independently. Keywords: guided inquiry learning, scaffolding techniques, self-efficacy.